KAJIAN EKONOMI DAN LINGKUNGAN AGRIBISNIS PETERNAKAN BABI DI KOTA TOMOHON (STUDI KASUS) - Sajow, Adrie Abram; Polii, Bobby; Laoh, Esry (Universitas Sam Ratulangi, 2014)
ABSTRACT ECONOMIC AND ENVINONMENT STUDY ON PIG FARMING AGRIBUSINESS IN TOMOHON CITY. (CASE STUDY).This study aims to analyze the feasibility of conventional (private) and environment (externalities) investment criteria, which determine the extent of the economic feasibility of the externalities investment criteria taking into account the private costs (conventional costs) and externalities costs (environmental costs) in the pig farm agribusiness. This research was conducted in Tomohon, where the sample pig farms that have business scale criterion of < 1,000 , 1,000-5,000 , and > 5,000 heads. The analysis used the analysis of investment criteria, with the calculation of Net Present Value (NPV), Benefit Cost Ratio (BCR) and Internal Rate of Return (IRR). NPV of conven-tionally and externalities was greater than zero or positive, these results suggest that the companies have been conventionally sampled financially feasibility, as well as the investment plan of externalities. IRR conventional and externalities is greaterthan one, these results indicate that the samples with conventional and externalities investment companies are still profitable, especially if the investment is viewed in the environment, it would be beneficial as it will reduce the environmental impact. BC ratio values conventionally and externalities is greater than one, these results suggest that the externalities investment is feasible for conducting. Keywords : Economic, Environment, Pig Farming, Tomohon